2007
DOI: 10.5194/acpd-7-8617-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rural continental aerosol properties and processes observed during the Hohenpeissenberg Aerosol Characterization Experiment (HAZE2002)

Abstract: Abstract. Detailed investigations of the chemical and microphysical properties of rural continental aerosols were performed during the HAZE2002 experiment, which was conducted in May 2002 at the Meteorological Observatory Hohenpeissenberg (DWD) in Southern Germany. The online measurement data and techniques included: size-resolved chemical composition of submicron particles by aerosol mass spectrometry (AMS); total particle number concentrations and size distributions over the diameter range of 3 nm to 9 μm (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…The m/z 44/OA ratio increases from 0.16 ± 0.003 (0.69 ± 0.022, equivalent O/C) in the free troposphere to 0.21 ± 0.004 (0.88 ± 0.019, equivalent O/C) in the upper troposphere and lower stratosphere, where m/z 29 makes up 45%, and m/z 44 contributes 21% to the total organic mass. Although the contribution of m/z 29 is higher than observed in other data, such organic mass spectra can be identified with the type “OOA‐1” [ Lanz et al , 2007; Ulbrich et al , 2009] or “LV‐OOA” (low‐volatile OOA) [ Jimenez et al , 2009] and similar mass spectra have been observed in the free troposphere before [ Hock et al , 2008]. In the volcanic aerosol layer, the ratio is slightly lower with 0.16 ± 0.003 (0.69 ± 0.021, equivalent O/C).…”
Section: Resultsmentioning
confidence: 65%
“…The m/z 44/OA ratio increases from 0.16 ± 0.003 (0.69 ± 0.022, equivalent O/C) in the free troposphere to 0.21 ± 0.004 (0.88 ± 0.019, equivalent O/C) in the upper troposphere and lower stratosphere, where m/z 29 makes up 45%, and m/z 44 contributes 21% to the total organic mass. Although the contribution of m/z 29 is higher than observed in other data, such organic mass spectra can be identified with the type “OOA‐1” [ Lanz et al , 2007; Ulbrich et al , 2009] or “LV‐OOA” (low‐volatile OOA) [ Jimenez et al , 2009] and similar mass spectra have been observed in the free troposphere before [ Hock et al , 2008]. In the volcanic aerosol layer, the ratio is slightly lower with 0.16 ± 0.003 (0.69 ± 0.021, equivalent O/C).…”
Section: Resultsmentioning
confidence: 65%
“…In a more polluted atmosphere near Pittsburgh, PA, ammonium and sulfate contributed the majority of condensable mass during the early stages of growth events; however, photochemically produced secondary organic aerosol (SOA) contributed significantly to growth during later stages of these events [Zhang et al, 2004[Zhang et al, , 2005. In contrast, Hock et al [2008] observed a growth event in rural southern Germany with significant mass contribution from aerosol nitrate.…”
Section: Introductionmentioning
confidence: 47%
“…atmospheric aerosol ͉ bioaerosol ͉ DNA analysis ͉ fungal spores R ecent studies have shown that fungal spores and other biological particles can account for large proportions of aerosol particle mass in pristine rainforest air as well as in rural and urban environments (1)(2)(3)(4)(5). For example, fungal spores were found to account for up to 45% of coarse particle mass (Ͼ1 m) in tropical rainforest air and up to 4-11% of fine particle mass (Յ2.5 m) in urban and rural air (3).…”
mentioning
confidence: 99%